Slow-release quantum dot tracer agent for oil field and preparation method

By using zinc source precursors, doped metal ions and oxygen group compounds, combined with epoxy resin and curing agent, the long-term and environmentally friendly problems of existing oilfield tracers were solved, and efficient, stable, green and environmentally friendly sustained release quantum dot tracers were prepared, which significantly improved the accuracy and effect of trace monitoring.

CN119662238APending Publication Date: 2025-03-21CNOOC ENERGY TECHNOLOGY & SERVICES LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411840105.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

Existing oilfield tracers have problems such as limited long-term traceability, environmentally friendly problems, limited detection accuracy, and performance differences caused by differences in molecular structure, which affect the trace monitoring results.

Method used

Quantum dot tracers with wide excitation wavelengths and narrow light spectrum were prepared using zinc source precursors, doped metal ions and oxygen group compounds, and mixed them with epoxy resin and curing agent to prepare sustained release quantum dot tracers by heating curing.

Benefits of technology

The prepared sustained-release quantum dot tracer has high fluorescence intensity, good chemical and thermal stability, green and environmentally friendly, and has consistent spectral performance under high temperature conditions, which significantly improves the performance and application effect of the tracer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119662238A_ABST
    Figure CN119662238A_ABST
Patent Text Reader

Abstract

The invention discloses a slow-release quantum dot tracer agent for an oil field and a preparation method. The slow-release quantum dot tracer for the oil field is characterized by comprising the following components in percentage by weight: 10-15% of a quantum dot material, 6-18% of a curing agent and 67-84% of epoxy resin, the quantum dot material is mainly prepared from a zinc source precursor, doped metal ions and an chalcogenide, wherein the molar ratio of the zinc source precursor to the doped metal ions to the chalcogenide is (8-10): (0.01-0.1): (10-25). The preparation method is simple, the reaction condition is mild, the raw materials are simple and easy to obtain, the wavelength of excitation light is controllable, and the application and popularization value is high.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of oil and gas field development, and in particular to a slow-release quantum dot tracer for oil fields and a preparation method thereof. Background Art

[0002] As an important part of the oilfield monitoring technology system, tracer monitoring technology has been used in various oilfields at home and abroad for many years. It has been widely used in many scenarios such as inter-well monitoring, fracturing monitoring, and production profile monitoring. It has formed multiple functions and technologies such as reservoir monitoring, wellbore monitoring, and ground monitoring. It can cover many aspects of oilfield production and is an important guarantee for the efficient development of oilfields. From the perspective of mechanism, oilfield tracers can be classified into inorganic salts, rare earth metal elements, organic trace substances, fluorescent tracers, radioactive isotope tracers, and stable isotope tracers. In summary, the above tracers still have many shortcomings, such as: limited long-term tracer effectiveness, environmental friendliness issues, limited detection accuracy, difficulty in improvement, performance differences caused by differences in molecular structure, affecting tracer monitoring results, etc. Summary of the invention

[0003] In order to solve the above technical problems, the present invention provides a slow-release quantum dot tracer for oil fields and a preparation method thereof. The quantum dot tracer has the characteristics of wide excitation wavelength and narrow light emission spectrum, good chemical stability and thermal stability, high fluorescence intensity, and green environmental protection.

[0004] In a first aspect, the present invention provides a slow-release quantum dot tracer for oil fields, which is achieved by adopting the following technical solution.

[0005] A slow-release quantum dot tracer for oil fields comprises the following components in weight percentage: 10-15% of quantum dot material, 6-18% of curing agent and 67-84% of epoxy resin; the quantum dot material is mainly prepared from a zinc source precursor, doped metal ions and an oxygen family compound, and the molar ratio of the zinc source precursor, the doped metal ions and the oxygen family compound is 8-10:0.01-0.1:10-25.

[0006] Furthermore, the zinc source precursor is selected from one or more of zinc chloride, anhydrous zinc acetate, zinc acetate dihydrate, zinc perchlorate, zinc stearate and zinc citrate dihydrate.

[0007] Furthermore, the doped metal ions are selected from one or more of copper ions, ferrous ions, cobalt ions, nickel ions, and indium ions.

[0008] Further, the oxygen compound is selected from sulfur, selenium, tellurium or a compound containing sulfur, selenium or tellurium. Specifically, the oxygen compound is selected from one or more of thioacetamide, thioglycolic acid, thiopropionic acid, thiourea, selenium dioxide, selenium powder, sodium selenate, sodium selenite, sodium selenide, diphenyl diselenide, tellurium dioxide, tellurium powder, sodium tellurate, sodium tellurite, sodium telluride and diphenyl ditelluride.

[0009] Furthermore, the preparation method of the quantum dot material is as follows:

[0010] S1. Add zinc source precursor, doping metal ions and oxygen compounds to water, stir evenly and fully dissolve;

[0011] S2 uses NaOH solution to adjust the solution pH ≥ 10 to obtain a Zn precursor solution;

[0012] S3. In a nitrogen atmosphere, add the Na2S aqueous solution to the Zn precursor solution while stirring, and heat the reaction solution to 100-110°C with stirring for 1-2h;

[0013] S4. After the reaction is completed, the system is cooled to room temperature, acetone is added to precipitate the quantum dots, and the purified quantum dots are obtained by centrifugation. The size of the quantum dot material is 2-20 nm.

[0014] Furthermore, in step S2, the mass fraction of the NaOH solution is 30%.

[0015] Furthermore, in step S3, the molar ratio of the zinc source precursor to Na2S is 8-10:10-25.

[0016] Furthermore, in step S3, the Na2S aqueous solution is replaced by mercaptopropionic acid and thiourea.

[0017] Furthermore, in step S4, the centrifugation condition is 5000-8000 rpm for 5 min.

[0018] Furthermore, the curing agent is selected from one or more of ethylenediamine, diethylenetriamine, polymethylenediamine, diethylaminopropylamine, high-carbon aliphatic diamines, aliphatic amide polyamines, m-xylene diamine, m-phenylenediamine, diaminodiphenylmethane, diaminodiphenyl sulfone, N-aminoethylpiperazine, and isophoronediamine.

[0019] In a second aspect, the present invention provides a method for preparing a sustained-release quantum dot tracer for oil fields, which is achieved by adopting the following technical solution.

[0020] A method for preparing the above-mentioned slow-release quantum dot tracer for oil fields comprises the following steps:

[0021] A specified amount of quantum dot material, curing agent and epoxy resin are heated and mixed evenly, poured into a mold and cured at 120-150° C. for 7-12 hours, and demolded to obtain a slow-release quantum dot tracer for oil fields.

[0022] Furthermore, the mold is a rectangular mold with a length of 15 cm, a width of 5 cm, and a thickness of 0.1 cm.

[0023] This application has the following beneficial effects.

[0024] The present invention adopts cheap and readily available raw materials and utilizes a gasification method with uniform reaction rate to controllably prepare water-soluble amorphous zinc sulfide quantum dots with strong biological activity and stable existence. Compared with the existing preparation method of water-soluble zinc sulfide quantum dots, the preparation method of the present invention is simple and controllable, the reaction conditions are mild, the raw materials are cheap and readily available, and it is environmentally friendly, and the obtained product has strong fluorescence performance and good biocompatibility. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 It is a physical picture of the tracer solution of Example 1 and Example 2 of the present invention (the left side is the tracer solution of Example 1; the right side is the tracer solution of Example 2);

[0026] Figure 2 is the quantum dot standard curve prepared in Example 1 of the present invention;

[0027] Figure 3 is the quantum dot standard curve prepared in Example 2 of the present invention;

[0028] Figure 4 is the quantum dot standard curve prepared in Comparative Example 1 of the present invention;

[0029] Figure 5 This is a comparison chart of light intensity of quantum dots statically adsorbed at 130°C for 36 hours in Example 1 of the present invention;

[0030] Figure 6 This is a comparison chart of light intensity of quantum dots statically adsorbed at 130°C for 36 hours in Example 2 of the present invention;

[0031] Figure 7 This is a comparison chart of light intensity of quantum dots in comparative example 1 of the present invention statically adsorbed at 130°C for 36 hours. DETAILED DESCRIPTION

[0032] The present patent application is further described below in conjunction with embodiments.

[0033] Example 1

[0034] A method for preparing a slow-release quantum dot tracer for oil fields, comprising the following steps:

[0035] S1. Add 20 mL of deionized water to a 100 mL beaker, then add 1 mmol of zinc chloride, 20 microliters of nickel chloride aqueous solution (0.01 mmol / L) and 1.6 mmol of mercaptopropionic acid, mix well to fully dissolve, and obtain a colorless clear solution;

[0036] S2, adding a 30% by mass NaOH aqueous solution dropwise to the solution prepared in step S1 until the pH of the solution is 11. During the addition of the NaOH solution, a large amount of white precipitate will first appear in the above solution. Continue to add NaOH until the precipitate is dissolved to obtain a colorless clear solution, thereby obtaining a Zn ion precursor solution;

[0037] S3, the Zn ion precursor solution obtained in step S2 was transferred to a 100 mL three-necked flask, and nitrogen protection was performed. Under stirring, a freshly prepared aqueous solution containing 0.1 mmol of Na2S was quickly added with a syringe, and the reaction solution was stirred and heated to 100°C and kept at a constant temperature for 1 hour;

[0038] S4. After the reaction is completed, the system is cooled to room temperature, 20 mL of acetone is added to convert the ZnS quantum dots into a precipitate, centrifuged at 8000 rpm for 5 min to obtain purified ZnS quantum dots, and dried at 105 °C;

[0039] S5. Mix the purified ZnS quantum dots, diethylenetriamine and epoxy resin in a mass ratio of 10:16:74, heat to 120°C to dissolve the epoxy resin, mix the system thoroughly, and cool after 12 hours to obtain a slow-release quantum dot tracer for oil fields.

[0040] Example 2

[0041] A method for preparing a slow-release quantum dot tracer for oil fields, comprising the following steps:

[0042] S1. Add 20 mL of deionized water to a 100 mL beaker, then add 1 mmol of zinc chloride, 20 microliters of cobalt chloride aqueous solution (0.01 mmol / L) and 1.6 mmol of mercaptopropionic acid, mix well to fully dissolve, and obtain a colorless clear solution;

[0043] S2, adding a 30% by mass NaOH aqueous solution dropwise to the solution prepared in step S1 until the pH of the solution is 11. During the addition of the NaOH solution, a large amount of white precipitate will first appear in the above solution. Continue to add NaOH until the precipitate is dissolved to obtain a colorless clear solution, thereby obtaining a Zn ion precursor solution;

[0044] S3, the Zn ion precursor solution obtained in step S2 was transferred to a 100 mL three-necked flask, and nitrogen protection was performed. Under stirring, a freshly prepared aqueous solution containing 0.1 mmol of Na2S was quickly added with a syringe, and the reaction solution was stirred and heated to 100° C. and kept at a constant temperature for 1 h;

[0045] S4. After the reaction is completed, the system is cooled to room temperature, 20 mL of acetone is added to convert the ZnS quantum dots into a precipitate, centrifuged at 8000 rpm for 5 min to obtain purified ZnS quantum dots, and dried at 105 °C;

[0046] S5. The purified ZnS quantum dots, polymethylene diamine and epoxy resin are mixed in a mass ratio of 10:18:72, heated to 140° C. to dissolve the epoxy resin, and the system is fully mixed. After 12 hours, the system is shaped and cooled to obtain a slow-release quantum dot tracer for oil fields.

[0047] Comparative Example 1

[0048] A method for preparing a slow-release quantum dot tracer for oil fields, comprising the following steps:

[0049] S1. Add 20 mL of deionized water to a 100 mL beaker, then add 1 mmol of zinc acetate and 1.6 mmol of mercaptopropionic acid, mix well to fully dissolve, and obtain a colorless clear solution.

[0050] S2, adding a 30% by mass NaOH aqueous solution dropwise to the solution prepared in S1, and continuing to add dropwise after a white precipitate appears until the precipitate is dissolved to obtain a colorless clear solution with a pH value ≥ 10, thereby obtaining a Zn ion precursor solution;

[0051] S3, the Zn ion precursor solution in step S2 was transferred to a 100 mL three-necked flask, and nitrogen protection was performed. Under stirring conditions, a freshly prepared aqueous solution containing 0.1 mmol of Na2S was quickly added with a syringe, and the reaction solution was stirred and heated to 100°C and kept at a constant temperature for 1 hour;

[0052] S4. After the reaction is completed, the system is cooled to room temperature, 20 mL of acetone is added to convert the ZnS quantum dots into a precipitate, centrifuged at 8000 rpm for 5 min to obtain purified ZnS quantum dots, and dried at 105 °C;

[0053] S5. The purified ZnS quantum dots, diethylaminopropylamine and epoxy resin are mixed in a mass ratio of 10:18:72, heated to 150° C. to dissolve the epoxy resin, and the system is fully mixed. After 12 hours, the system is shaped and cooled to obtain the slow-release quantum dot tracer for oil fields.

[0054] Performance Testing

[0055] (1) Compatibility test

[0056] 10000 mg / L sodium chloride solution was used to prepare the tracer solutions of Example 1 and Example 2 with a concentration of 1 ppm. After standing for 24 hours at room temperature, the quantum dots were mixed with the 10000 mg / L sodium chloride solution without stratification, precipitation, or flocculant formation, indicating good compatibility (see Figure 1 ).

[0057] (2) Drawing of standard curve

[0058] ① Use pure water to prepare the standard solution of Example 1, and take the maximum light intensity under each concentration range to draw a standard curve; the standard curve is as follows Figure 2 shown.

[0059] ② Use pure water to prepare the standard solution of Example 2, and take the maximum light intensity under each concentration range to draw a standard curve; the standard curve is as follows Figure 3 shown.

[0060] ③ Use pure water to prepare the standard solution of comparative example 1, and take the maximum light intensity under each concentration range to draw a standard curve; the standard curve is as follows Figure 4 shown.

[0061] from Figure 2 , 3 It can be seen that quantum dot tracers can form a linear relationship within a certain detection range.

[0062] (3) Static adsorption experiment under well temperature conditions

[0063] ① Prepare a water-soluble quantum dot mixture, wherein the dosage of Example 1 and Example 2 is 1 ppm respectively, and test the light intensities Q1 and Q3;

[0064] ② Weigh 10g of 60-80 mesh sandstone powder sample into an aging tank, add the quantum dot tracer mixture at a ratio of 1:3 (mass), stir evenly, and place in a 130℃ oven for 36h;

[0065] ③ Gently shake, take the upper clear liquid to perform the light intensity test Q1-2 and Q3-2 of Example 1 and Example 2, and then compare with Q1 and Q3 respectively, calculate the light intensity retention rate, and the experimental results are shown in Figure 5-7 The light intensity retention rate of Example 1 is 103%, and the light intensity retention rate of Example 2 is 131%.

[0066]

[0067] After being statically placed at 130°C for 36 hours, the light intensity of the quantum dots in the embodiment and the comparative example changed; the characteristic fluorescence emission spectrum of the quantum dots remained consistent with that at room temperature, and the spectral performance of the quantum dots was not affected by the well temperature; the reasons for the enhanced light intensity of the quantum dots: high temperature promoted the solubility of the quantum dots in water, resulting in an increase in light intensity; or high temperature made the quantum dot transition more active, resulting in an increase in light intensity.

[0068] The embodiments of this specific implementation method are all preferred embodiments of the present invention, and are not intended to limit the protection scope of the present invention. Therefore, all equivalent changes made according to the principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A slow-release quantum dot tracer for oil fields, characterized in that: The invention comprises the following components in weight percentage: 10-15% of quantum dot material, 6-18% of curing agent and 67-84% of epoxy resin; the quantum dot material is mainly prepared from zinc source precursor, doped metal ions and oxygen family compound, and the molar ratio of zinc source precursor, doped metal ions and oxygen family compound is 8-10:0.01-0.1:10-25.

2. The sustained-release quantum dot tracer for oil fields according to claim 1, characterized in that: The zinc source precursor is selected from one or more of zinc chloride, anhydrous zinc acetate, zinc acetate dihydrate, zinc perchlorate, zinc stearate and zinc citrate dihydrate.

3. The slow-release quantum dot tracer for oil fields according to claim 1, characterized in that: The doped metal ions are selected from one or more of copper ions, ferrous ions, cobalt ions, nickel ions, and indium ions.

4. The slow-release quantum dot tracer for oil fields according to claim 1, characterized in that: The oxygen compound is selected from sulfur, selenium, tellurium or a compound containing sulfur, selenium or tellurium.

5. The slow-release quantum dot tracer for oil fields according to claim 1, characterized in that: The preparation method of the quantum dot material is as follows: S1. Add zinc source precursor, doping metal ions and oxygen compounds to water, stir evenly and fully dissolve; S2 uses NaOH solution to adjust the solution pH ≥ 10 to obtain a Zn precursor solution; S3. In a nitrogen atmosphere, add the Na2S aqueous solution to the Zn precursor solution while stirring, and heat the reaction solution to 100-110°C with stirring for 1-2h; S4. After the reaction is completed, the system is cooled to room temperature, acetone is added to precipitate the quantum dots, and the purified quantum dots are obtained by centrifugation.

6. The slow-release quantum dot tracer for oil fields according to claim 5, characterized in that: In step S3, the molar ratio of the zinc source precursor to Na2S is 8-10:10-25.

7. The slow-release quantum dot tracer for oil fields according to claim 5, characterized in that: In step S3, the Na2S aqueous solution is replaced by mercaptopropionic acid and thiourea.

8. The slow-release quantum dot tracer for oil fields according to claim 1, characterized in that: The curing agent is selected from one or more of ethylenediamine, diethylenetriamine, polymethylenediamine, diethylaminopropylamine, high carbon number aliphatic diamine, aliphatic amide polyamine, m-xylene diamine, m-phenylenediamine, diaminodiphenylmethane, diaminodiphenyl sulfone, N-aminoethylpiperazine, and isophoronediamine.

9. A method for preparing the slow-release quantum dot tracer for oil fields according to any one of claims 1 to 8, characterized in that: The following steps are involved: A specified amount of quantum dot material, curing agent and epoxy resin are heated and mixed evenly, poured into a mold and cured at 120-150° C. for 7-12 hours, and demolded to obtain a slow-release quantum dot tracer for oil fields.

Citation Information

Cited By

  • Tracing use method of trace substances in complex horizon in oil field

    CN122257801A